(untitled) (Journal of Economic Research & Business Administration, 2016)
Entrepreneurs have to operate under conditions of uncertainty, ex- posed to risks. Success in business can be achieved by the use of the proj- ect approach. The article discusses the choice of approach to risk management busi- ness to ready technology, standards, or to develop its own methodology, based on its own business practice. The article gives the definition of the concept of the project, project management, and operational and project management processes, sum- marized characteristics of the project approach. Also, it’s considers using international practices the business risks management. It’s also emphasizes that risk management process tools and risk management projects tools are nearly identical.